2016
DOI: 10.1159/000448806
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with Quality of Life in Long-Term Care Residents with Dementia: A Cross-Sectional Study

Abstract: Background: To determine which characteristics are associated with quality of life (QOL) in residents with moderate to very severe dementia in long-term care facilities (LTCFs). Material and Methods: This was a cross-sectional analysis of a cluster randomized controlled study in 12 Dutch LTCFs that enrolled 288 residents, with moderate to severe dementia assessed with the Reisberg Global Deterioration Scale (Reisberg GDS) and QOL with the QUALIDEM. Characteristics that were hypothesized to be associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 74 publications
6
58
3
2
Order By: Relevance
“…However, our data do not support this hypothesis. An association between ADL and QoL has been reported in previous studies [10, 11, 12]. Thus, we hypothesised that previous studies found a significant association whereas we did not because ADL is more important for certain domains of QoL rather than for overall QoL, such as the “well-being” subscale of the QUALID scale, as considered previously [10], or the QUALID “comfort” subscale [11].…”
Section: Discussionmentioning
confidence: 66%
“…However, our data do not support this hypothesis. An association between ADL and QoL has been reported in previous studies [10, 11, 12]. Thus, we hypothesised that previous studies found a significant association whereas we did not because ADL is more important for certain domains of QoL rather than for overall QoL, such as the “well-being” subscale of the QUALID scale, as considered previously [10], or the QUALID “comfort” subscale [11].…”
Section: Discussionmentioning
confidence: 66%
“…The internal consistency between the caregiver’s and the patient’s responses have been reported to be excellent [9]. Concurrent validity is indicated by strong correlations with other scales associated with the activities of daily living level and the degree of depression [9, 11-13]. The QoL-AD appears to be the most researched among all the instruments [10].…”
Section: Introductionmentioning
confidence: 99%
“…Failure to do so may result in a denial of appropriate medication or therapeutic intervention, prescription of analgesics at inadequate dosages, or use of inappropriate medication (e.g., antipsychotics) [15-20]. These may lead to poor quality of life and premature death in these individuals [21-25]. Assessing pain requires a tool with sound psychometric properties and innovative characteristics so that timely access to appropriate pain management is assured.…”
Section: Introductionmentioning
confidence: 99%